Analisis Kebijakan Pendidikan Islam di Negara Konflik: Studi Kasus di Thailand - Fahmi Anwar Nasution (TADRIBUNA, 2023)
Thailand consists of two parts with different religions, ethnicities, regions and cultures. The north is known as the Kingdom of Thailand, and the south is mostly a devout Muslim. The aim of this research is to analyze Thailand's Islamic education policy. the methods used by qualitative studies are qualitative methods, and there is a document study. The research results are as follows. Thailand was originally associated with the short-lived kingdom of Sukhothai, which existed in 1238. After the collapse of this kingdom, it was succeeded by the Ayutthaya dynasty (14th century). The kingdom experienced a winning system because the area was a trade route for European countries. Thailand's Political Situation In the 1930's, there was a change in the government system. The montane system no longer exists. Monthon Pattani is divided into three states: Pattani, Yarra and Narathiwat. Each Muang (province) becomes a Changwat (province) and is directly supervised by the central government of Bangkok. Thai Islamic Education Policy and System; a) Surau and Mosque systems; b) Traditional Pondok System; c) Madrasa system; d) Malay School System/TADIKA (Kindergartens) and e) Modern Pondok Pesantren System (Private Islamic Education Schools). The Impact of Politics on Thailand's Education Development, management of the education system is under one roof: leadership, management, education staff , and curriculum type, each with two groups that serve two goals for the same student. In terms of leadership, it is still under the auspices of the Ulama of Patani. The aim of the Thai government is to reform the education sector with two models